2008
DOI: 10.1161/circimaging.108.769786
|View full text |Cite
|
Sign up to set email alerts
|

Direct En Face Imaging of Secundum Atrial Septal Defects by Velocity-Encoded Cardiovascular Magnetic Resonance in Patients Evaluated for Possible Transcatheter Closure

Abstract: Background-Atrial septal defect (ASD) flow can be measured indirectly by velocity-encoded cardiovascular magnetic resonance (veCMR) of the pulmonary artery and aorta. Imaging the secundum ASD en face could potentially enable direct flow measurement and provide valuable information about ASD size, shape, location, and proximity to other structures. Methods and Results-Forty-four patients referred for possible transcatheter ASD closure underwent a comprehensive standard evaluation, including transesophageal and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 39 publications
(46 reference statements)
0
40
0
Order By: Relevance
“…Through‐plane ASD flow, in the en face view, was successfully visualized as described previously (8–10). Figure 8 shows the en face view of a large ASD with white cross hairs defining its size and cross‐sectional shape.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through‐plane ASD flow, in the en face view, was successfully visualized as described previously (8–10). Figure 8 shows the en face view of a large ASD with white cross hairs defining its size and cross‐sectional shape.…”
Section: Resultsmentioning
confidence: 99%
“…SLC has potential application in the preprocedure assessment of ASD for closure device sizing and for excluding improper candidates. A previous study has shown that en face PC is superior to intracardiac echocardiography for device sizing and that CMR identifies those with anatomy unsuitable for percutaneous closure (10). Because PC has the disadvantage that a high velocity encoding setting may suppress the edges of a low velocity jet leading to underestimation of orifice size, SLC may theoretically provide a better estimation of ASD size as it is not susceptible to this potential error.…”
Section: Discussionmentioning
confidence: 99%
“…Velocity encoded contrast cine imaging was not performed in this study, however, this is another CMR technique that can provide information about the size and shape of the atrial septal defect [16,18] as well as provide accurate assessment of shunt magnitude from measuring flow in the systemic and pulmonary circulations [20,21]. However, this technique has not been used for the assessment of margins due to its limited spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of pulmonary veins prior to radiofrequency ablation for atrial fibrillation/left atrial and pulmonary venous anatomy including dimensions of veins for mapping purposes (Level of evidence: B, Appropriateness criteria: A) 246) reported that CMR provided information incremental to comprehensive standard evaluation that altered clinical management in 20% of patients. Recently, the catheter-based percutaneous aortic valve replacement has been introduced and the number of this procedure being performed has increased markedly.…”
Section: )mentioning
confidence: 99%